Pelatihan Pengelolaan Kelas Interaktif Berbasis Smartphone bagi Guru-Guru SMP Negeri 7 Kota Jambi: Training on Smartphone Based Interactive Classroom Management for Teacher at SMPN 7 Jambi City - Hidayati, Hidayati; Sartika, Delita; Kurniawan, Dedy; Al Arif, Tubagus Zam Zam; Ulfiati, Lilik; Armiwati, Armiwati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
According to research by a digital marketing research institution, the number of smartphone users in Indonesia has increased significantly each year. In 2016, the number of users stood at 65.2 million people and continued to rise, reaching 92 million people in 2019. However, this dramatic increase has not been accompanied by education on smartphone use, leading to various cases of cellphone misuse among students. The service team recognized the need for training on effective mobile phone use, particularly in schools. SMP Negeri 7 Kota Jambi (State Junior High School 7 of Jambi City) was selected as the service location based on the availability of supporting facilities, especially adequate internet infrastructure. This community service took place on August 5, 2020, using lecture, discussion, demonstration, and hands-on practice simulation methods, attended by 40 teachers from various subject areas. Initial survey results showed that only 2 out of 40 teachers knew about the learning applications Kahoot, Mentimeter, and Quizizz, but had never implemented them in teaching. The final evaluation results showed that 100% of teachers understood how to use interactive smartphone-based learning applications, and 90% expressed interest in integrating them into their teaching.